Morphology and ultrastructure of the adult ovarian cycle in Mithracidae (Crustacea, Decapoda, Brachyura, Majoidea) - Mollemberg, Michelle; Zara, Fernando Jose [UNESP]; Santana, William (Biomed Central Ltd, 2017)
The ultrastructure of the ovary during development and yolk production is poorly known in Brachyura and Majoidea in particular. Here, we describe the histology, histochemistry and ultrastructure of the adult ovarian cycle in four Mithracidae species from three different genera: Mithrax hispidus, Mithrax tortugae, Mithraculus forceps and Omalacantha bicornuta. All species showed a similar pattern of ovarian development and vitellogenesis. Macroscopically, we detected three stages of ovarian development: rudimentary (RUD), developing (DE) and mature (MAT); however, in histological and ultrastructural analyses, we identified four stages of development. The oocytes of the RUD stage, during endogenous vitellogenesis, have basophilic cytoplasm filled with dilated rough endoplasmic reticulum. The reticulum lumen showed many granular to electron-dense materials among the different stages of development. The Golgi complexes were only observed in the RUD stage and are responsible for releasing vesicles that merge to the endogenous or immature yolk vesicles. At the early DE stage, the oolemma showed many coated and endocytic vesicles at the cortex. The endocytic vesicles merge with the endogenous yolk to form the exogenous or mature yolk vesicles, always surrounded by a membrane, characterizing exogenous vitellogenesis. The exogenous yolk vesicles comprise glycoproteins, showing only neutral polysaccharides. At the late DE stage, endocytosis still occurs, but the amount of endogenous yolk decreases while the exogenous yolk increases. The late DE stage is characterized by the beginning of chorion production among the microvilli. The MAT stage is similar to the late DE, but the endogenous yolk is restricted to a few cytoplasmic areas, the ooplasma is filled with exogenous yolk, and the oolemma has very few coated vesicles. In the MAT stage, the chorion is fully formed and shows two electron- dense layers. The ovarian development of the species studied has many similarities with the very little known Majoidea in terms of the composition, arrangement and increment of the yolk vesicles during oocyte maturation. The main differences are in the vitellogenesis process, where immature yolk formation occurs without the direct participation of the mitochondria but with the participation of the rough endoplasmic reticulum in the endogenous phase.
Keywords: Histology; Mithrax; Mithraculus; Omalacantha; Transmission electron microscopy